How do you evaluate a lambda expression in Haskell? - parsing

Lambdas have the form: (lambda (var) expr) and represent an anonymous function that takes a single argument. There are no multi-argument functions in MiniRacket.
data Expr
= LambdaExpr String Expr
| LetExpr String Expr Expr
deriving (Show, Eq)
Evaluating a lambda should result in a closure, which is the function body, the name of the argument to it, and the current environment when the function was defined. This environment is then used when applying the function because it should let us know which bindings were available up until that point.
Here is my evalLambdaExpr
-- evaluate lambdas, which requires storing the current environment as the closure,
-- this should result in a ClosureVal, which can later be used for apply, if it's
-- a totally anonymous function, then "" is the function name, otherwise if it was
-- built with a let expression, then the let name is its name.
evalLambdaExpr :: Evaluator Value
evalLambdaExpr = do
(env, LambdaExpr letName valexpr) <- next
case getValue (eval evalExpr (env, valexpr)) of
Right (ClosureVal "" argName funBody cenv) ->
let env = Env.bind "" (ClosureVal "" argName funBody cenv) cenv
in case getValue (eval evalExpr (env, funBody)) of
Right v -> return v
Left err -> evalError err
Right nameval ->
case getValue (eval evalExpr (bind letName nameval env, valexpr)) of
Right letval -> return letval
Left err -> evalError err
Left err -> evalError err
-- and an Alternative ...
instance Alternative Evaluator where
empty = failEval "no matching evaluation"
-- define the type for values, which in our mini language
-- can be integers, bools, pairs, or closures
data Value
= IntVal Integer
| BoolVal Bool
| PairVal (Value, Value)
| ClosureVal String String Expr ValueEnv
deriving (Show, Eq)
newtype Evaluator a = E {eval :: (ValueEnv, Expr) -> Either ErrorT (a, (ValueEnv, Expr))}
-- this is the basic evaluator, it ends when ast is an EmptyExpr, but otherwise,
-- we get the the environment and expr returned
next :: Evaluator (ValueEnv, Expr)
next =
E
( \parserState -> case parserState of
(_, EmptyExpr) -> Left $ EvalError "no more expressions"
(env, x) -> Right ((env, x), (env, EmptyExpr))
)
evalError :: ErrorT -> Evaluator a
evalError err = E (\_ -> Left err)
My evalLambdaExpr is always returning a Left; why is that?
As an example, my evalLetExpr is working correctly and this is what I have:
-- Evaluate a let expression. This first evaluates the
-- argument to the identifier. Once that is evaluated, I
-- bind the value to the name in a new environment, then
-- I evaluate the body with this new environment
evalLetExpr :: Evaluator Value
evalLetExpr = do
(env, LetExpr letName valexpr body) <- next
case getValue (eval evalExpr (env, valexpr)) of
-- we got a closure from it, but it doesn't have a name,
-- so let's add that to the closure as its 'funname'
Right (ClosureVal "" argName funBody cenv) ->
let env' = Env.bind letName (ClosureVal letName argName funBody cenv) cenv
in case getValue (eval evalExpr (env', body)) of
Right v -> return v
Left err -> evalError err
Right nameval ->
case getValue (eval evalExpr (bind letName nameval env, body)) of
Right letval -> return letval
Left err -> evalError err
Left err -> evalError err
For both evaluators, I commented what they do on above them. Why is evalStr "(lambda (x) true)" returning Left (EvalError "no matching evaluation")?
I know it's not my parsing because that works.

evalLambdaExpr :: Evaluator Value
evalLambdaExpr = do
(env, LambdaExpr letName valexpr) <- next
case getValue (eval evalExpr (env, valexpr)) of
Hmm. As far as I understand, this says that in order to evaluate (lambda (x) (+ x 1)), we should evaluate (+ x 1) immediately. That is not what should happen -- the body of the lambda should only be evaluated when the closure is applied -- after all, we don't even know what the value of x should be in that expression.
I am not sure if this is what is causing your error, but I would expect this to cause all sorts of weird things to happen as you try to evaluate expressions at the wrong time with unbound variables.
One typically needs an Expr constructor for applying a lambda to an argument.

Related

Invalid exception messages from parser combinators in Haskell

I'm studying functional programming using Haskell language. And as an exercise I need to implement a function parsing a primitive arithmetic expression from String. The function must be able to handle double literals, operations +, -, *, / with the usual precedence and parentheses.
parseExpr :: String -> Except ParseError Expr
with next defined data types:
data ParseError = ErrorAtPos Natural
deriving Show
newtype Parser a = P (ExceptState ParseError (Natural, String) a)
deriving newtype (Functor, Applicative, Monad)
data Prim a
= Add a a
| Sub a a
| Mul a a
| Div a a
| Abs a
| Sgn a
deriving Show
data Expr
= Val Double
| Op (Prim Expr)
deriving Show
Where ExceptState is a modified State monad, allowing to throw exception pointing at the error position.
data Annotated e a = a :# e
deriving Show
infix 0 :#
data Except e a = Error e | Success a
deriving Show
data ExceptState e s a = ES { runES :: s -> Except e (Annotated s a) }
Also ExceptState has defined Functor, Applicative and Monad instances, which were thoroughly tested earlier, so I am positive in their correctness.
instance Functor (ExceptState e s) where
fmap func ES{runES = runner} = ES{runES = \s ->
case (runner s) of
Error err -> Error err
Success ans -> Success (mapAnnotated func $ ans) }
instance Applicative (ExceptState e s) where
pure arg = ES{runES = \s -> Success (arg :# s)}
p <*> q = Control.Monad.ap p q
instance Monad (ExceptState e s) where
m >>= f = joinExceptState (fmap f m)
where
joinExceptState :: ExceptState e s (ExceptState e s a) -> ExceptState e s a
joinExceptState ES{runES = runner} = ES{runES = \s ->
case (runner s) of
Error err -> Error err
Success (ES{runES = runner2} :# s2) ->
case (runner2 s2) of
Error err -> Error err
Success (res :# s3) -> Success (res :# s3) }
To implement the function parseExpr I used basic parser combinators:
pChar :: Parser Char
pChar = P $ ES $ \(pos, s) ->
case s of
[] -> Error (ErrorAtPos pos)
(c:cs) -> Success (c :# (pos + 1, cs))
parseError :: Parser a
parseError = P $ ES $ \(pos, _) -> Error (ErrorAtPos pos)
instance Alternative Parser where
empty = parseError
(<|>) (P(ES{runES = runnerP})) (P(ES{runES = runnerQ})) =
P $ ES $ \(pos, s) ->
case runnerP (pos, s) of
Error _ -> runnerQ (pos, s)
Success res -> Success res
instance MonadPlus Parser
which were used to construct more complex ones:
-- | elementary parser not consuming a character, failing if input doesn't
-- reach its end
pEof :: Parser ()
pEof = P $ ES $ \(pos, s) ->
case s of
[] -> Success (() :# (pos, []))
_ -> Error $ ErrorAtPos pos
-- | parses a single digit value
parseVal :: Parser Expr
parseVal = Val <$> (fromIntegral . digitToInt) <$> mfilter isDigit pChar
-- | parses an expression inside parenthises
pParenth :: Parser Expr
pParenth = do
void $ mfilter (== '(') pChar
expr <- parseAddSub
(void $ mfilter (== ')') pChar) <|> parseError
return expr
-- | parses the most prioritised operations
parseTerm :: Parser Expr
parseTerm = pParenth <|> parseVal
parseAddSub :: Parser Expr
parseAddSub = do
x <- parseTerm
ys <- many parseSecond
return $ foldl (\acc (sgn, y) -> Op $
(if sgn == '+' then Add else Sub) acc y) x ys
where
parseSecond :: Parser (Char, Expr)
parseSecond = do
sgn <- mfilter ((flip elem) "+-") pChar
y <- parseTerm <|> parseError
return (sgn, y)
-- | Parses the whole expression. Begins from parsing on +, - level and
-- successfully consuming the whole string.
pExpr :: Parser Expr
pExpr = do
expr <- parseAddSub
pEof
return expr
-- | More convinient way to run 'pExpr' parser
parseExpr :: String -> Except ParseError Expr
parseExpr = runP pExpr
As a result, at this point function works as intended if given String expression is valid:
ghci> parseExpr "(2+3)-1"
Success (Op (Sub (Op (Add (Val 2.0) (Val 3.0))) (Val 1.0)))
ghci> parseExpr "(2+3-1)-1"
Success (Op (Sub (Op (Sub (Op (Add (Val 2.0) (Val 3.0))) (Val 1.0))) (Val 1.0)))
Otherwise ErrorAtPos does not point at the necessary position:
ghci> parseExpr "(2+)-1"
Error (ErrorAtPos 1)
ghci> parseExpr "(2+3-)-1"
Error (ErrorAtPos 1)
What am I doing wrong here? Thank you in advance.
My main assumption was that something wrong was with function (<|>) of Alternative Parser and it incorrectly changed pos variable.
(<|>) (P(ES{runES = runnerP})) (P(ES{runES = runnerQ})) =
P $ ES $ \(pos, s) ->
case runnerP (pos, s) of
-- Error _ -> runnerQ (pos, s)
Error (ErrorAtPos pos') -> runnerQ (pos' + pos, s)
Success res -> Success res
But it led to more strange results:
ghci> parseExpr "(5+)-3"
Error (ErrorAtPos 84)
ghci> parseExpr "(5+2-)-3"
Error (ErrorAtPos 372)
Then more doubts were aimed at joinExceptState function of instance Monad (ExceptState e s) in spite of everything I've run it through, doubts that it wasn't working on s of (Natural, String) type as I indented in this case. But then I can't really change it for this concrete type only.
Excellent question, although it would have been even better if it really included all your code. I filled in the missing pieces:
mapAnnotated :: (a -> b) -> Annotated s a -> Annotated s b
mapAnnotated f (a :# e) = (f a) :# e
runP :: Parser a -> String -> Except ParseError a
runP (P (ES {runES = p})) s = case p (0, s) of
Error e -> Error e
Success (a :# e) -> Success a
Why is parseExpr "(5+)-3" equal to Error (ErrorAtPos 1)? Here's what happens: we call parseExpr which (ultimately) calls parseTerm which is just pParenth <|> parseVal. pParenth fails, of course, so we look at the definition of <|> to work out what to do. That definition says: if the thing on the left fails, try the thing on the right. So we try the thing on the right (i. e. parseVal), which also fails, and we report the second error, which is in fact at position 1.
To see this more clearly, you can just replace pParenth <|> parseVal with parseVal <|> pParenth and observe that you get ErrorAtPos 2 instead.
This is almost certainly not the behaviour you want. The documentation of Megaparsec's p <|> q, here, says:
If [parser] p fails without consuming any input, parser q is tried.
(emphasis in original, meaning: parser q is not tried in other cases). This is a more useful thing to do. If you got reasonably far trying to parse a parenthesised expression and then got an error, probably you want to report that error rather than complaining that '(' isn't a digit.
Since you say this is an exercise, I'm not going to tell you how to fix the problem. I'll tell you some other stuff, though.
First, this is not your only issue with error reporting. Above we see that parseVal "(1" reports an error at position 1 (after the problematic character, which is at position 0) whereas pParenth "(5+)-3" reports an error at position 2 (before the problematic character, which is at position 3). Ideally, both should give the position of the problematic character itself. (Of course, it'd be even better if the parser stated what character it expected, but that's more difficult to do.)
Second, the way I found the problem was to import Debug.Trace, replace your definition of pChar with
pChar :: Parser Char
pChar = P $ ES $ \(pos, s) -> traceShow (pos, s) $
case s of
[] -> Error (ErrorAtPos pos)
(c:cs) -> Success (c :# (pos + 1, cs))
and mull over the output for a bit. Debug.Trace is sometimes less useful than one hopes, because of lazy evaluation, but for a program like this it can help a lot.
Third, if you modify your definition of <|> to match Megaparsec's does, you might need Megaparsec's try combinator. (Not for the grammar you're trying to parse now, but maybe later.) try solves the issue that
(singleChar 'p' *> singleChar 'q') <|> (singleChar 'p' *> singleChar 'r')
fails on the string "pr" with Megaparsec's <|>.
Fourth, you sometimes write someParser <|> parseError, which I think is equivalent to someParser for both your definition of <|> and Megaparsec's.
Fifth, you don't need void; just ignore the result, it's the same thing.
Sixth, your Except seems to just be Either.

Making Let binding parsing in Haskell

I want to create parser-like behaviour in Haskell such that I can assign an expression to a variable based on a string. I have difficulties doing so.
If I have types with the following definitions:
data Expr =
Numb Int
| Add Expr Expr
| Let {var :: PVariable, definition, body :: Expr}
type PVariable = String
And want to create a function 'eval' that would be able to handle different operations such as Add, Subtract, Multiply etc... but also the Let binding, sucht that 'eval' would be subject to the following definition:
eval :: Exp -> Integer
eval (Number expr) = expr
eval (Add expr1 expr2) = eval(expr1) + eval(expr2)
...
eval (Let v expr1 body) = ...
How could I then create eval such that it would assign an expr1 to the string v, that would then be expressed in the body, such that the parser-like behaviour could accomplish for instance something similar to the conversion from:
Let {var = "Var1", definition = expr1, body = (Add (Var "Var1") (Var "Var1"))}
where expr1 would be a chosen expression such that the above could be expressed as
let Var1 = expr1 in expr1+expr1
That could then have different Expr assigned to expr1 such as (Numb 2), so that we would get something similar to the following in Haskell:
let Var1 = 2 in Var1 + Var1
So far I have tried to deal with isolating fields of the record 'Let' so that I can evaluate each of these considering that I want to stay with the function type declarations. But I don't think that this is the easiest way, and it would probably require that I create a whole function to extract these, as far as I can see from : How to generically extract field names and values in Haskell records
Is there a smarter way to go about it?
You'll need the function eval to have extra argument that would contain the variable bindings and pass it to subexpressions recursively. You also need a special case to evaluate Var-expressions:
module Main where
import qualified Data.Map as M
data Expr =
Numb Int
| Add Expr Expr
| Let {var :: PVariable, definition, body :: Expr}
| Var PVariable
type PVariable = String
type Env = M.Map PVariable Int
eval :: Env -> Expr -> Int
eval _ (Numb a) = a
eval env (Add e1 e2) = (eval env e1) + (eval env e2)
eval env (Var v) = M.findWithDefault (error $ "undefined variable: " ++ v) v env
eval env (Let v expr body) = let
val = eval env expr
env' = M.insert v val env
in eval env' body
main = print $ eval M.empty $ Let "a" (Numb 1) (Add (Var "a") (Numb 2))

How to parse a boolean expression in Haskell?

I have a file called Parser.hs and have defined methods for evaluating a boolean expression. In that file, I have the following:
-- implementing parsing bool operations, these are 'and' and 'or'
parseBoolOp :: Parser BoolOp
parseBoolOp =
do symbol "and" >> return And
<|> do symbol "or" >> return Or
-- a bool expression is the operator followed by one or more expressions that we have to parse
-- TODO: add bool expressions
boolExpr :: Parser Expr
boolExpr = BoolExpr <$> parseBoolOp <*> (pure <$> parseExpr)
-- the main parsing function which alternates between all the options you have
parseExpr :: Parser Expr
parseExpr =
do
parseAtom
<|> parseParens notExpr
<|> parseParens boolExpr
<|> parseParens parseExpr
In another file called Eval.hs, I have defined the following methods. I am trying to evaluate a bool expr using calcBoolList and evalListOfExprs:
-- call them whenever I want to generate an error
evalError :: ErrorT -> Evaluator a
evalError err = E (\_ -> Left err)
-- this evaluates a list of expressions and returns a list of values
-- by mapping an evaluator function (using <$>) over the list of expressions
evalListOfExprs :: ValueEnv -> [Expr] -> [Either ErrorT Value]
evalListOfExprs env exprs =
( \expr ->
case eval evalExpr (env, expr) of
Right (res, _) -> Right res
Left msg -> Left msg
)
<$> exprs
-- evaluates a bool expression, this first evaluates all the
-- arguments to the bool expression and then uses calcBoolList
-- to calculate the boolean operation over the arguments. Note that
-- first, I use evalListOfExprs to evaluate the arguments. Then
-- I used calcBoolList with the right op on it
evalBoolExpr :: Evaluator Value
evalBoolExpr = do
(env, BoolExpr op exprs) <- next
-- TODO: implement the rest!
case calcBoolList op (evalListOfExprs env exprs) of
Right v1 -> return v1
Left err -> evalError err
-- determine which bool operation to use to fold with by the kind of BoolOp passed in
calcBoolList :: BoolOp -> [Either ErrorT Value] -> Either ErrorT Value
calcBoolList op lst = case op of
And -> boolOpFold (&&) lst
Or -> boolOpFold (||) lst
-- parses the string then evaluates it
parseAndEval :: String -> Either ErrorT (Value, (ValueEnv, Expr))
parseAndEval str = do
(ast, _) <- parse parseExpr str
-- here, [] represents the empty environment
eval evalExpr ([], ast)
-- parseAndEvalEnv = parseAndEvalEnv [] -- could replace the code above with this <-- because we defined parseAndEvalEnv below
-- parseAndEvalEnv :: ValueEnv -> String -> Either ErrorT (Value, (ValueEnv, Expr))
-- parseAndEvalEnv env str = do
-- (ast, _) <- parse parseExpr str
-- -- here, [] represents the empty environment
-- eval evalExpr ([], ast)
-- extract the value from the result, which contains extra stuff we don't need to see
getValue :: Either ErrorT (Value, (ValueEnv, Expr)) -> Either ErrorT Value
getValue (Right (val, _)) = Right val
getValue (Left err) = Left err
-- takes a string and parses it, then it tries to evaluate it
evalStr :: String -> Either ErrorT Value
evalStr = getValue . parseAndEval
The expressions types and value types are contained in this file called Expr.hs:
-- define the operator types
data BoolOp = And | Or deriving (Show, Eq)
-- define the expression types
data Expr
= BoolExpr BoolOp [Expr]
deriving (Show, Eq)
-- define the type for values, which in our mini language
-- can be integers, bools, pairs, or closures
data Value
= BoolVal Bool
deriving (Show, Eq)
When I run evalStr "(and true (and false true) true)", which should return Right (BoolVal False), it instead returns Left (ParseError "'a' didn't match expected character"). Is my evaluator wrong or is it the boolExpr in my Parser file?
Your boolExpr doesn't address and x y. You write
boolExpr = BoolExpr <$> parseBoolOp <*> (pure <$> parseExpr)
which means to parse an operator, and then parse exactly one expression, and wrap that expression in a singleton list (here pure :: a -> [a]). You probably want something like
boolExpr = BoolExpr <$> parseBoolOp <*> parseExpr `sepBy1` spaces
to allow multiple subexpressions.

Haskell: Graham Hutton Book Parsing (Ch-8): What does `parse (f v) out` do, and how does it do it?

My question is about Graham Hutton's book Programming in Haskell 1st Ed.
There is a parser created in section 8.4, and I am assuming anyone answering has the book or can see the link to slide 8 in the link above.
A basic parser called item is described as:
type Parser a = String -> [(a, String)]
item :: Parser Char
item = \inp -> case inp of
[] -> []
(x:xs) -> [(x,xs)]
which is used with do to define another parser p (the do parser)
p :: Parser (Char, Char)
p = do x <- item
item
y <- item
return (x,y)
the relevant bind definition is:
(>>=) :: Parser a -> (a -> Parser b) -> Parser b
p >>= f = \inp -> case parse p inp of
[] -> []
[(v,out)] -> parse (f v) out
return is defined as:
return :: a -> Parser a
return v = \inp -> [(v,inp)]
parse is defined as:
parse :: Parser a -> String -> [(a,String)]
parse p inp = p inp
The program (the do parser) takes a string and selects the 1st and 3rd characters and returns them in a tuple with the remainder of the string in a list, e.g., "abcdef" produces [('a','c'), "def"].
I want to know how the
(f v) out
in
[(v,out)] -> parse (f v) out
returns a parser which is then applied to out.
f in the do parser is item and item taking a character 'c' returns [('c',[])]?
How can that be a parser and how can it take out as an argument?
Perhaps I am just not understanding what (f v) does.
Also how does the do parser 'drop' the returned values each time to operate on the rest of the input string when item is called again?
What is the object that works its way through the do parser, and how is it altered at each step, and by what means is it altered?
f v produces a Parser b because f is a function of type a -> Parser b and v is a value of type a. So then you're calling parse with this Parser b and the string out as arguments.
F in the 'do' parser is item
No, it's not. Let's consider a simplified (albeit now somewhat pointless) version of your parser:
p = do x <- item
return x
This will desugar to:
p = item >>= \x -> return x
So the right operand of >>=, i.e. f, is \x -> return x, not item.
Also how does the 'do' parser 'drop' the returned values each time to operate on the rest of the input string when item is called again? What is the object that works its way through the 'do' parser and how is it altered and each step and by what means is it altered?
When you apply a parser it returns a tuple containing the parsed value and a string representing the rest of the input. If you look at item for example, the second element of the tuple will be xs which is the tail of the input string (i.e. a string containing all characters of the input string except the first). This second part of the tuple will be what's fed as the new input to subsequent parsers (as per [(v,out)] -> parse (f v) out), so that way each successive parser will take as input the string that the previous parser produced as the second part of its output tuple (which will be a suffix of its input).
In response to your comments:
When you write "p = item >>= \x -> return x", is that the equivalent of just the first line "p = do x <- item"?
No, it's equivalent to the entire do-block (i.e. do {x <- item; return x}). You can't translate do-blocks line-by-line like that. do { x <- foo; rest } is equivalent to foo >>= \x -> do {rest}, so you'll always have the rest of the do-block as part of the right operand of >>=.
but not how that reduces to simply making 'out' available as the input for the next line. What is parse doing if the next line of the 'do' parser is a the item parser?
Let's walk through an example where we invoke item twice (this is like your p, but without the middle item). In the below I'll use === to denote that the expressions above and below the === are equivalent.
do x <- item
y <- item
return (x, y)
=== -- Desugaring do
item >>= \x -> item >>= \y -> return (x, y)
=== -- Inserting the definition of >>= for outer >>=
\inp -> case parse item inp of
[] -> []
[(v,out)] -> parse (item >>= \y -> return (v, y)) out
Now let's apply this to the input "ab":
case parse item "ab" of
[] -> []
[(v,out)] -> parse (item >>= \y -> return (v, y)) out
=== Insert defintiion of `parse`
case item "ab" of
[] -> []
[(v,out)] -> parse (item >>= \y -> return (v, y)) out
=== Insert definition of item
case ('a', "b") of
[] -> []
[(v,out)] -> parse (item >>= \y -> return (v, y)) out
===
parse (item >>= \y -> return ('a', y)) out
Now we can expand the second >>= the same we did the fist and eventually end up with ('a', 'b').
The relevant advice is, Don't panic (meaning, don't rush it; or, take it slow), and, Follow the types.
First of all, Parsers
type Parser a = String -> [(a,String)]
are functions from String to lists of pairings of result values of type a and the leftover Strings (because type defines type synonyms, not new types like data or newtype do).
That leftovers string will be used as input for the next parsing step. That's the main thing about it here.
You are asking, in
p >>= f = \inp -> case (parse p inp) of
[] -> []
[(v,out)] -> parse (f v) out
how the (f v) in [(v,out)] -> parse (f v) out returns a parser which is then applied to out?
The answer is, f's type says that it does so:
(>>=) :: Parser a -> (a -> Parser b) -> Parser b -- or, the equivalent
(>>=) :: Parser a -> (a -> Parser b) -> (String -> [(b,String)])
-- p f inp
We have f :: a -> Parser b, so that's just what it does: applied to a value of type a it returns a value of type Parser b. Or equivalently,
f :: a -> (String -> [(b,String)]) -- so that
f (v :: a) :: String -> [(b,String)] -- and,
f (v :: a) (out :: String) :: [(b,String)]
So whatever is the value that parse p inp produces, it must be what f is waiting for to proceed. The types must "fit":
p :: Parser a -- m a
f :: a -> Parser b -- a -> m b
f <$> p :: Parser ( Parser b ) -- m ( m b )
f =<< p :: Parser b -- m b
or, equivalently,
p :: String -> [(a, String)]
-- inp v out
f :: a -> String -> [(b, String)]
-- v out
p >>= f :: String -> [(b, String)] -- a combined Parser
-- inp v2 out2
So this also answers your second question,
How can that be a parser and how can it take out as an argument?
The real question is, what kind of f is it, that does such a thing? Where does it come from? And that's your fourth question.
And the answer is, your example in do-notation,
p :: Parser (Char, Char)
p = do x <- item
_ <- item
y <- item
return (x,y)
by Monad laws is equivalent to the nested chain
p = do { x <- item
; do { _ <- item
; do { y <- item
; return (x,y) }}}
which is a syntactic sugar for the nested chain of Parser bind applications,
p :: Parser (Char, Char) -- ~ String -> [((Char,Char), String)]
p = item >>= (\ x -> -- item :: Parser Char ~ String -> [(Char,String)]
item >>= (\ _ -> -- x :: Char
item >>= (\ y -> -- y :: Char
return (x,y) )))
and it is because the functions are nested that the final return has access to both y and x there; and it is precisely the Parser bind that arranges for the output leftovers string to be used as input to the next parsing step:
p = item >>= f -- :: String -> [((Char,Char), String)]
where
{ f x = item >>= f2
where { f2 _ = item >>= f3
where { f3 y = return (x,y) }}}
i.e. (under the assumption that inp is a string of length two or longer),
parse p inp -- assume that `inp`'s
= (item >>= f) inp -- length is at least 2 NB.
=
let [(v, left)] = item inp -- by the def of >>=
in
(f v) left
=
let [(v, left)] = item inp
in
let x = v -- inline the definition of `f`
in (item >>= f2) left
=
let [(v, left)] = item inp
in let x = v
in let [(v2, left2)] = item left -- by the def of >>=, again
in (f2 v2) left2
=
..........
=
let [(x,left1)] = item inp -- x <- item
[(_,left2)] = item left1 -- _ <- item
[(y,left3)] = item left2 -- y <- item
in
[((x,y), left3)]
=
let (x:left1) = inp -- inline the definition
(_:left2) = left1 -- of `item`
(y:left3) = left2
in
[((x,y), left3)]
=
let (x:_:y:left3) = inp
in
[((x,y), left3)]
after few simplifications.
And this answers your third question.
I am having similar problems reading the syntax, because it's not what we are used to.
(>>=) :: Parser a -> (a -> Parser b) -> Parser b
p >>= f = \inp -> case parse p inp of
[] -> []
[(v,out)] -> parse (f v) out
so for the question:
I want to know how the (f v) out in [(v,out)] -> parse (f v) out returns a parser which is then applied to out.
It does because that's the signature of the 2nd arg (the f): (>>=) :: Parser a -> (a -> Parser b) -> Parser b .... f takes an a and produces a Parser b . a Parser b takes a String which is the out ... (f v) out.
But the output of this should not be mixed up with the output of the function we are writing: >>=
We are outputting a parser ... (>>=) :: Parser a -> (a -> Parser b) ->
Parser b .
The Parser we are outputting has the job of wrapping and chaining the first 2 args
A parser is a function that takes 1 arg. This is constructed right after the first = ... i.e. by returning an (anonymous) function: p >>= f = \inp -> ... so inp refers to the input string of the Parser we are building
so what is left is to define what that constructed function should do ... NOTE: we are not implementing any of the input parsers just chaining them together ... so the output Parser function should:
apply the input parser (p) to the its input (inp): p >>= f = \inp -> case parse p inp of
take the output of that parse [(v, out)] -- v is the result, out is what remains of the input
apply the input function (f is (a -> Parser b)) to the parsed result (v)
(f v) produces a Parser b (a function that takes 1 arg)
so apply that output parser to the remainder of the input after the first parser (out)
For me the understanding lies in the use of destructuring and the realization that we are constructing a function that glues together the execution of other functions together simply considering their interface.
Hope that helps ... it helped me to write it :-)

Parser Error Reporting deriving the right instances

I am trying to build an error reporting parser in haskell. Currently I have been looking at a tutorial and this is what I have so far.
type Position = (Int, Int)
type Err = (String, Position)
newtype Parser1 a = Parser1 {parse1 :: StateT String (StateT Position (MaybeT
(Either Err))) a} deriving (Monad, MonadState String, Applicative, Functor)
runParser :: Parser1 a -> String -> Either Err (Maybe ((a, String), Position))
runParser p ts = runMaybeT $ runStateT (runStateT (parse1 p) ts) (0, 0)
basicItem = Parser1 $ do
state <- get
case state of
(x:xs) -> do {put xs; return x}
[] -> empty
item = Parser1 $ do
c <- basicItem
pos <- lift get
lift (put (f pos))
return c
f :: Char -> Position -> Position
f d (ln, c) = (ln + 1, 0)
f _ (ln, c) = (ln , c + 1)
This piece of code does not compile, I think it is to do with my item parser and the fact that I am trying to access the inner state namely position. I was wondering how in the deriving clause do I make Haskell derive the instances for both states in my parser type, so then I can access the inner state?
Edit 1:
I initially tried declaring basicItem as:
basicItem :: (MonadState String m, Alternative m) => m t
basicItem = do
state <- get
case state of
(x:xs) -> do {put xs; return x}
[] -> empty`
However, I kept getting the error:
I was wondering why it cannot deduce context of get from MonadState String m,
when in my deriving clause I have MonadState String.
The error for my initial question is here:

Resources